Hormônios tireoidianos, TSH, desempenho e qualidade de carcaça e carne em suínos imunocastrados alojados em diferentes sistemas de criação - Carrazza, Leonardo Gomes (2012)
This study aimed to evaluate the influence of pig housing systems on serum concentrations of triiodothyronine (T3), thyroxine (T4) and thyroid stimulating hormone (TSH), correlating with characteristics of animal performance, meat quality and carcass. Therefore, 48 male pigs with an average age of 84 days were divided into two distinct housing systems, the Intensive System of Rearing Pig (conventional system) and the Intensive System of Swine Raised Outdoors (SISCAL), being 24 animals per environment divided into six plots of four pigs each. The experiment lasted 105 days. Blood was collected at the beginning and end of the experiment when the animals were sent to slaughter in a slaughterhouse, where it proceeded to collect material and data for analysis. There were no statistical differences between the two systems, for percentage of intramuscular fat (GIM), pH 45 minutes, pH 24 hours, Intestinal length (CI), carcass length (CC), Backfat Thickness 1 (ET1), Backfat Thickness 2 (ET2), Backfat Thickness in Half Moon (ETML) Hot Carcass Weight (PCQ), carcass yield (RC) and Lean Meat Yield (RCM). Animals housed on the conventional system had higher values of weight gain (GP) (63.49 vs. 54.14 kg, P <0.05) and Average Daily Weight Gain (GPMD) (0.6163 vs. 0, 5255 kg P <0.05) than animals raised on SISCAL. The TSH serum level increased from the beginning to the end of the experiment (0.12 to 0.30 μIU, P <0.05), whereas T4 decreased (6.44 to 3.11 mg/dL, P <0.05) did not differing between the two systems. The T3 level at the end of the housing was higher at SISCAL than in the conventional system (vs. 1.10. 0.75 ng/mL) at P <0.05. The concentrations of T3 and T4 had correlation of 0.48, while moderate and negative correlations were found between the levels of T3 and features of PCQ (-0.48), GP (-0, 48) and ET2 (-0.39) and between T4 and PCQ (-0.53), GP (-0.57) and ET2 (-0.34) P<0.005.